ARTIFICIAL DIETS PREFERENCE OF STINGLESS BEE, TETRAGONULA PEGDENI SCHWARZ - Matintarangson, Nathapong; Wattanuruk, Duangduan (PSRU Journal of Science and Technology, 2024)
The objective of this research was to study the artificial diets preference of stingless bee (Tetragonula pagdeni Schwarz). The stingless bee nest was placed in the center of the experimental house and surrounded by artificial diets in order to the stingless bee to choose preference of​ artificial diets. All 7 artificial diet formula were as follows: 1 water (control), 2 glucose (40 ml), 3 fructose (40 ml), 4 glucose (20 ml) + fructose (20 ml), 5 glucose (35 ml)+ soybean (20 g) + pollen (5 g), 6 fructose (35 ml) + soybean (20 g) + pollen (5 g) and 7 glucose (32 ml) + fructose (32 ml) + soybean (20 g) + pollen (5 g). The results found that the artificial diet 7 (glucose + fructose + soybean + pollen) had the highest of number of stingless bee and was significantly effective (P<0.05) when compared with the control. The number of stingless bees was 25.41 ± 0.90 adults/hour. Therefore, the use of artificial diet can replace natural diet during the rainy season when there is not enough food. Farmers can culture the stingless bee in order to obtain quality honey that will continue to create careers and income